Fully-automated radiosynthesis of the amyloid tracer [11C] PiB via direct [11C]CO2 fixation-reduction - Pablo Buccino; Eduardo Savio; Williams Porcal (SpringerOpen, 2019)
Abstract Background The β-amyloid radiotracer [11C] PiB is extensively used for the Positron Emission Tomography (PET) diagnosis of Alzheimer's Disease and related dementias. For clinical use, [11C] PiB is produced using the 11C-methylation method ([11C] Methyl iodide or [11C] methyl triflate as 11C-methylation agents), which represents the most employed 11C-labelling strategy for the synthesis of 11C-radiopharmaceuticals. Recently, the use of direct [11C]CO2 fixation for the syntheses of 11C-tracers has gained interest in the radiochemical community due to its importance in terms of radiochemical versatility and for permitting the direct employment of the cyclotron-produced precursor [11C]CO2. This paper presents an optimised alternative one-pot methodology of [11C]CO2 fixation-reduction for the rapid synthesis of [11C] PiB using an automated commercial platform and its quality control. Results [11C] PiB was obtained from a (25.9 ± 13.2)% (Average ± Variation Coefficient, n = 3) (end of synthesis, decay corrected) radiochemical yield from trapped [11C]CO2 after 1 min of labelling time using PhSiH3 / TBAF as the fixation-reduction system in Diglyme at 150 °C. The radiochemical purity was higher than 95% in all cases, and the molar activity was (61.4 ± 1.6) GBq/μmol. The radiochemical yield and activity (EOS) of formulated [11C] PiB from cyclotron-produced [11C]CO2 was (14.8 ± 12.1)%, decay corrected) and 9.88 GBq (± 6.0%), respectively. These are higher values compared to that of the 11C-methylation method with [11C]CH3OTf (~ 8.3%). Conclusions The viability of the system PhSiH3 / TBAF to efficiently promote the radiosynthesis of [11C] PiB via direct [11C]CO2 fixation-reduction has been demonstrated. [11C] PiB was obtained through a fully automated radiosynthesis with a satisfactory yield, purity and molar activity. According to the results, the one-pot methodology employed could reliably yield sufficiently high tracer amounts for preclinical and clinical use.